Sistem Pakar dalam Mendiagnosis Gizi Buruk pada Balita dengan Menggunakan Metode CBR - Sandi Alam; Gunadi Widi Nurcahyo (Jurnal Sistim Informasi dan Teknologi, 2022)
Limited information makes people have little knowledge of the early symptoms of Malnutrition in Toddlers. This disease must be treated quickly from an early age otherwise it will not get worse. This study aims to accurately diagnose the symptoms to provide fast, precise and accurate information in classifying the types of Malnutrition in Toddlers. This research is an expert system using Case Based Reasoning (CBR) method. The CBR method makes decisions from new cases based on solutions from previous cases. The data processed were 22 symptoms and 8 types of disease for 22 cases. The accuracy results are very good by being able to identify all types of malnutrition. So that this research can be used as a recommendation in speed to identify malnutrition in toddlers quickly.